EFL learner identity construction across socio-cultural structure and learner agency: a case of marginalised Dalit adolescents in rural Nepal - Kamal Raj Devkota (Cogent Education)
This article unpacks how socio-cultural structure and learner agency regularly interplay in the identity construction of Dalit adolescents in an English-as-a-Foreign-Language (EFL) setting in rural Nepal. ‘Learner agency’ stands as an individual’s capacity to exercise to make choices, take control, self-regulate, and constitute his/her identity in school. Based on critical ethnography, this research applies interviews, participant observation and life history to collect data and portray Dalit adolescents, stressing how they navigate their identity in an EFL classroom and school. The analysis reveals that the socio-culturally constituted identity ‘Dalit’ (the lowest caste following the Classical Hindu Caste system) and its complex intersection with social class and gender always force these adolescents to feel structured at a low position in their society. However, the learner agency that they exercise while engaging in classroom activities prepares them to enact newer identity(-ies) in schools, EFL classrooms and broader society.